Sistem Pendukung Kepuntusan Penentuan Varietas Bawang Merah Menggunakan Metode Simple Additive Weighting (SAW) di Desa Bonto Lojong Kab. Bantaeng - Alfiani, Ananda; Lukman Anas; Lukman (Universitas Muhammadiyah Makassar, 2025)
ANANDA ALFIANI. Decision Support System for Determining Shallot Varieties Using the Saw Method (Simple Additive Weighting) in Bonto Lojong Village, Kab. Bantaeng (Supervised by Lukman Anas, S.Kom., MT., and Lukman SKM, S.Kom., MT.,).The research carried out aimed to determine the types of shallot varieties in Bantaeng Regency, especially in Bonto Lojong Village, which was web-based. This system helps shallot farmers in selecting suitable varieties to be used as seeds using the Simple Additive Weighting (SAW) method. The research design used is Unified Modeling Language (UML) which is designed in a structured manner consisting of use case diagram model designs, activity diagrams, sequence diagrams and class diagrams. The text editor used in building this system is Sublime Text, while the programming language uses PHP, JavaScript and MySQL for database processing. In this research, data collection was obtained through observation, interviews and documentation. The method used in the research is the Simple Additive Weighting (SAW) method. Results from the application of the Decision Support System for Determining Shallot Varieties Using the Saw Method (Simple Additive Weighting) in Bonto Lojong Village, Kab. Bantaeng helps and makes it easier for farmers to determine the variety of shallots in their land by giving the highest value to the types of shallot varieties to be used as seeds for the next planting period. Keywords: Decision support system, spk of shallot varieties, SAW method.